Translator's Style Through Lexical Bundles: A Corpus-Driven Analysis of Two English Translations of Hongloumeng - Liu, Kanglong; Afzaal, Muhammad (Frontiers in Psychology, 2021)
Based on a corpus-driven analysis of two translated versions of Hongloumeng (one by David Hawkes and the other by Xianyi Yang and Gladys Yang) in parallel corpora, this paper investigates the use of lexical bundles in an attempt to trace the stylistic features and differences in the translations produced by the respective translators. The Hongloumeng corpus is developed at the sentence level to facilitate co-occurrence of the source texts and the two corresponding translations. For this purpose, the 3-word and 4-word lexical bundles were first extracted and then analyzed with respect to the functional classification proposed by Biber et al. (2004). The results of the study show that Hawkes’ translation is embedded with a greater number and variety of lexical bundles than the one by the Yang couple. The study also identifies the differences between the two versions which can be traced back to the translators’ deployment of different translation strategies, appearing in turn to be influenced by the translators’ language backgrounds, the translation skopos and settings and the social, political and ideological milieu in which the translations were produced.